Preparação, caracterização e avaliação in vitro de compósitos baseados em quitosana, fibroína e hidroxiapatita para a engenharia tecidual óssea - Lima, Paulo Autran Leite (2012)
Hybrid composites with chitosan (CHI), fibroin (SF) and hydroxyapatite (HA) are biocompatible and attractive for bone engineering applications. The objective of this work was to prepare, to characterize and to evaluate in vitro cells behavior in contact with CHI, CHI/SF and CHI/SF/HA scaffolds. The biomaterials were produced from a CHI, CHI/SF, CHI/SF/HA solution in acetic acid and, after the production process, they were submitted the in vitro tests with STRO+1A, MC3T3-E1 and SaOS-2 cells for 07, 14 and 21 days. The scaffolds were characterized by X-ray diffraction, attenuated total reflection Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, scanning electron microscopy and energy dispersive spectroscopy. In addition, tests of porosity, pore size and contact angle were performed. Cell viability and activity were assessed by MTT reduction and alkaline phosphate activity detection. It was possible to prepare scaffolds 3D based on chitosan, fibroin and hydroxyapatite and the interaction between this materials were observed by physicochemical characterization. The composites were considered non-toxic and they were capable to promote cell adhesion, proliferation and differentiation. Additionally, they may be used in the therapy of bone defect repair.